Capsulotomy in Unstable Slipped Capital Femoral Epiphysis and the Odds of AVN: A Meta-analysis of Retrospective Studies. Issue 6 (July 2019) - Kaushal, Neil; Chen, Cynthia; Agarwal, Kunal N.; Schrader, Tim; Kelly, Derek; Dodwell, Emily R.
Abstract : Background: Unstable slipped capital femoral epiphysis (SCFE) may lead to avascular necrosis (AVN) in up to 60% of patients. The aim of this study was to assess the best clinical evidence to determine the effect of capsular decompression (CD) on odds of AVN in unstable SCFE. Methods: Medline, Embase, and Cochrane databases were systematically searched for comparative studies investigating AVN rates in unstable SCFE treated with or without CD (aspiration, percutaneous, or open). Quality was evaluated by the Newcastle Ottawa Scale. A comparative analysis with pooled effect estimates using random-effects modeling was calculated. Secondary analysis pooled AVN rates from both comparative studies and case series. Results: Comparative analysis included 17 retrospective studies with 453 hips (201 with CD, 252 without CD). Thirty-four of 201 (17%) hips with CD developed AVN, while 67 of 252 (27%) hips without CD developed AVN. The odds of AVN for patients treated with or without CD [odds ratio=0.80, 95% confidence interval (CI): 0.48-1.35] was not statistically different. Subanalysis on patients treated with in situ pinning or positional reduction and pinning showed no difference in AVN rates with or without CD (odds ratio=0.97, 95% CI: 0.44-2.10). In the secondary analysis of 17 comparative studies and 23 case series, the average rate of AVN was 17%, 0.17 (95% CI: 0.13-0.23) for patients treated with CD (60/447 hips) and 28%, 0.28 (95% CI: 0.22-0.35) for patients treated without CD (129/464 hips). Conclusions: There was no statistically significant decrease in odds of AVN with CD. However, studies were limited by their retrospective nature and inadequate documentation of CD techniques; the majority lacked femoral head blood flow monitoring to demonstrate adequate decompression. Future prospective studies with carefully documented complete decompression may help to elucidate the effect of CD on AVN risk. Although there was no statistically different odds of AVN with or without CD, even this large meta-analysis was underpowered, and one cannot conclude that there was truly no difference in odds of AVN without an appropriately powered study. Therefore, we recommend routine CD for all unstable SCFEs pending additional research, as CD adds little to the surgical procedure and may minimize the risk of a devastating insult to the femoral head. Abstract : Supplemental Digital Content is available in the text.